Virtualized and Personalized Financial Management Education Enabled by Mobile Interactive Technologies - Li, Liyang (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Against the backdrop of the deep integration of mobile technologies and educational digitalization, financial management education has been constrained by insufficient levels of virtualization, limited adaptability to individual learners, and inadequate real-time interactive experiences. Existing educational frameworks have struggled to reconcile the computational constraints of mobile devices with the demands of immersive learning environments. To address these challenges, an intelligent education framework centered on mobile devices and organized around a collaborative three-layer architecture was proposed, with the objective of transcending the limitations of traditional instructional models and enabling deeply virtualized and personalized financial management education tailored to the lightweight and ubiquitous characteristics of mobile technologies. Through the coordinated operation of a mobile interactive terminal layer, an edge intelligence layer, and a cloud-based intelligent hub layer, the proposed framework emphasizes innovations in intelligent mobile interaction design, dynamic allocation of edge–cloud computational resources, and multimodal data-driven personalized adaptation. A closed-loop, collaborative, personalized learning ecosystem is thereby constructed. Prototype system evaluations demonstrate that the proposed framework effectively enhances learning immersion, personalization, and learning efficiency in mobile learning scenarios, providing a novel technological paradigm for the deployment of mobile intelligent education in professional disciplines.